Modern aspects of treatment for patients with atrial fibrillation (a literature review) - O. V. Shershnyova; І. О. Стецюк; O. O. Lisova; T. О. Hawker (Zaporožskij Medicinskij Žurnal)
The aim of the work is to analyze and summarize the data of the scientific literature which highlight modern approaches to the management of patients with atrial fibrillation (AF).